Cabinet Reshuffle News for 2020 in Van Leeweun's Critical Discourse Analysis - Dedi Sahputra (Britain International for Academic Research (BIAR-Publisher), 2021)
Political events, especially those related to public policy, are the consumption of mass media to be presented in the form of news to the public. In reconstructing events into news, the mass media has the potential to be influenced by various interested parties. Theo Van Leewuen's critical discourse analysis is a model that can be used to critically analyze the effects that occur in the presentation of news in the mass media. Through text analysis, this critical discourse analysis model will inform about the various strategies used in compiling news texts. The object of this research is kompas.com news entitled